2022
DOI: 10.3389/fphar.2022.826261
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Antidiabetic Effect of Pistacia atlantica Leaves by Activity-Guided Fractionation and Phytochemical Content Analysis by LC-QTOF-MS

Abstract: In this study, the antidiabetic, antiobesity, antioxidant, and antihyperlipidemic effects potential of Pistacia atlantica Desf. leaves were evaluated by in vitro methods. The effects of the leaves of the plant on pancreatic lipase, pancreatic cholesterol esterase, and PTP1B enzymes were investigated for the first time and it was observed that leaf methanol extract (IC50: 123.67 ± 0.40 μg/ml) and n-hexane sub-extract (IC50: 61.03 ± 0.11 μg/ml) had much stronger effects on pancreatic cholesterol esterase enzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Phytochemical studies have evidenced that terpenes as the main components of various plants are capable of exerting BG-lowering effects. It has been also reported that monoterpenes content of PA such as α-pinene and β-pinene, could act as potent inhibitors of α-amylase and α-glucosidase (Kasabri et al, 2011;Pekacar, 2022). It seems that oleic and linoleic acid in PA oil has a suitable effect on glycemic indices F I G U R E 9 Forest plot of standardized mean difference (SMD) and 95% confidence interval (CI) in malondialdehyde (MDA) between intervention and comparison group following the consumption of PA (Pistacia atlantica).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phytochemical studies have evidenced that terpenes as the main components of various plants are capable of exerting BG-lowering effects. It has been also reported that monoterpenes content of PA such as α-pinene and β-pinene, could act as potent inhibitors of α-amylase and α-glucosidase (Kasabri et al, 2011;Pekacar, 2022). It seems that oleic and linoleic acid in PA oil has a suitable effect on glycemic indices F I G U R E 9 Forest plot of standardized mean difference (SMD) and 95% confidence interval (CI) in malondialdehyde (MDA) between intervention and comparison group following the consumption of PA (Pistacia atlantica).…”
Section: Discussionmentioning
confidence: 99%
“…Phytochemical studies have evidenced that terpenes as the main components of various plants are capable of exerting BG‐lowering effects. It has been also reported that monoterpenes content of PA such as α‐pinene and β‐pinene, could act as potent inhibitors of α‐amylase and α‐glucosidase (Kasabri et al, 2011; Pekacar, 2022). It seems that oleic and linoleic acid in PA oil has a suitable effect on glycemic indices based on the observations about the consumption of a diet high with these fatty acids (Garg, 1994; Jamshidi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have been conducted to demonstrate the wide range of pharmacological activities at the expense of P. atlantica , including antibacterial [ 10 , 11 , 12 ], antioxidant [ 11 , 12 , 13 , 14 ], antidiabetic [ 14 , 15 , 16 ], anti-inflammatory [ 12 , 17 ], hepatoprotective [ 18 ], antitumor [ 19 , 20 ], anti-acetylcholinesterase [ 21 , 22 ], and antihyperlipidemic effects [ 23 ]. In fact, there are various chemical compounds in this plant species that may justify its potential therapeutic role, including triterpenoids, flavonoids, other phenolic compounds, tannins, fatty acids, and phytosterols [ 4 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The various parts of the Atlas pistachio, including the resin, leaves, fruits and galls, have been used for a long time in diverse regions as efficient remedies for a wide range of diseases. For instance, leaves, gull, and gum resin have a wound-healing effect and have been used to treat digestive and gastrointestinal disorders, diabetes, Alzheimer, hepatic, kidney, and brain diseases [1][2][3][4]. The Atlas pistachio's fruits are also a very abundant source of bioactive compounds [5,6].…”
Section: Introductionmentioning
confidence: 99%